2010
DOI: 10.1007/s00415-010-5864-1
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial ghrelin response is reduced in patients with Parkinson’s disease and idiopathic REM sleep behaviour disorder: a peripheral biomarker for early Parkinson’s disease?

Abstract: Ghrelin, an orexigenic peptide, has multiple functions, which include promoting gastrointestinal motility and influencing higher brain functions. Experimental data suggest that ghrelin has neuroprotective potential in the MPTP mouse model of Parkinson's disease (PD). PD patients show delayed gastric emptying and other symptoms that may relate to disturbed excretion of ghrelin. No data are available on postprandial ghrelin response in patients with PD and idiopathic REM sleep behaviour disorder (iRBD)--a condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 24 publications
5
52
2
3
Order By: Relevance
“…Although about a half of the patients suffering from Parkinson's disease experience reduced intestinal motility (29), it is likely because of decreased cholinergic and increased catecholaminergic stimulation (30), and dopaminergic medication (31). The study by Unger et al (32) pointed out the decrease in ghrelin signaling under this catecholaminergic and dopaminergic overstimulation, whereas it should be also noted that Karasawa et al (33) reported confl icting fi ndings in a similar experimental Parkinsonism model. Interestingly, no change in fasting ghrelin in vagotomized patients (34) suggests that disturbed cholinergic transmission is not a determinant for lowered ghrelin levels in Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although about a half of the patients suffering from Parkinson's disease experience reduced intestinal motility (29), it is likely because of decreased cholinergic and increased catecholaminergic stimulation (30), and dopaminergic medication (31). The study by Unger et al (32) pointed out the decrease in ghrelin signaling under this catecholaminergic and dopaminergic overstimulation, whereas it should be also noted that Karasawa et al (33) reported confl icting fi ndings in a similar experimental Parkinsonism model. Interestingly, no change in fasting ghrelin in vagotomized patients (34) suggests that disturbed cholinergic transmission is not a determinant for lowered ghrelin levels in Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/259333 doi: bioRxiv preprint first posted online Feb. 5, 2018; Mechanistically, we reasoned that as circulating levels of acyl-ghrelin and UAG have opposing actions on neurogenesis and cognition in mice, there should be a reduction in the plasma ratio of acyl-ghrelin to UAG (AG:UAG) in humans diagnosed with dementia. As acyl-ghrelin protects against neuron loss in models of Parkinson's disease (PD) 30,31 and is reportedly reduced in human PD 32,33 , we hypothesized that circulating AG:UAG ratios C.…”
Section: Resultsmentioning
confidence: 99%
“…The utility of ghrelin in Parkinson's models may reflect not only neuroprotection, but also an up-regulatory impact of ghrelin on dopamine synthesis and release in healthy neurons [59]. Decreased ghrelin secretion has been reported in patients with Parkinson's and Alzheimer's, and this might play a role not only in neurodegeneration, but also the weight loss that commonly accompanies these disorders [62][63][64]. A markedly decreased expression of both ghrelin and GOAT has been observed in the temporal lobe of Alzheimer's patients [65].…”
Section: Ghrelin's Role In Cognition and Neuroprotectionmentioning
confidence: 98%